AZABODIPY aggregates as a promising electroluminescent material for sustainable NIR OLED applications. Issue 7 (16th March 2023) - Mróz, Wojciech; Squeo, Benedetta Maria; Vercelli, Barbara; Botta, Chiara; Pasini, Mariacecilia
Abstract : AZABODIPY with thiophene and phenyl substituents allows electroluminescence in pure NIR to be achieved. Abstract : Organic materials capable of emission in the near infrared (NIR) spectral range are of great interest for many branches of science and technology. In this work we investigate a NIR emitting molecule (DTDPAB ) based on 4, 4-difluoro-4-bora-3 a, 4 a -diaza- s -indacene (BODIPY) modified with nitrogen substitution at the carbon meso position (AZABODIPY) and thiophens and phenyls substituents. The thienyl substituents decrease the energy band gap of the molecule with respect to standard AZABODIPY and the emission spectrum results strongly shifted to the lower energies. The molecule is employed as a dopant in commercial and suitably synthesized polymers used as hosts in solution-processable emitting layers of organic light-emitting diodes (OLEDs). After device architecture optimization the electroluminescence in pure NIR (>700 nm) with the maximum at 910 nm is achieved. To our knowledge, this is the first example of electroluminescence from a single AZABODIPY emitter in real NIR, which adds another type of electrically excitable organic luminophore to the family of NIR emitting materials.